Kemudahan Penggunaan Fitur Aplikasi E-Commerce terhadap Perilaku Konsumtif Mahasiswa - Agistia Nurbani Rajaba; Ahnaf Daris Fadhilah; Anatasya Jelita Putri Dirgantara; Fitriyani Dwi Azzahra; Hopid Jidan; Najwa Ananda Mariana; Rama Wijaya Abdul Rozak (Jurnal Riset Ekonomi dan Akuntansi, 2024)
The ease of use of E-commerce application features raises problems among students in the aspect of consumptive behavior. The main objective of this study is to assess the impact of using E-commerce on consumptive behavior among students in Indonesia. The method used in this research is quantitative research method. The scale in this study uses a Likert scale, which is a measurement method to measure the perceptions, attitudes, or opinions of individuals or groups about social events or phenomena. Data collection was carried out by distributing questionnaires using google forms through social media such as Whatsapp, Instagram, and Twitter. From the research data, 107 respondents were obtained from all students in Indonesia who used the E-commerce application, the majority of respondents were female with the age of 19 years. The results show that the ease of access to E-commerce affects consumptive behavior among students, especially because of the many promos and discounts that are easily obtained through the E-commerce application. In addition, this study also highlights the significant role of features such as shopping carts, promos and discounts, product searches and reviews in shaping the consumptive behavior of its users.